(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Social Media has become the most important tool for interpersonal interactions in today’s world and its application has led the human interaction to assume greater magnitude, impacting everything around us. The world of business and commerce has also seen opportunities in this field and most importantly the Marketing area sees it as a platform to reach consumers effectively. Various researches have shown that social media marketing (SMM) efforts are effective in building the Consumer based brand equity (CBBE) and Purchase intention (PI) of the consumers and this indicates the role of cyber world in marketing area. The digital marketing and social media marketing are the new age media tools that have revolutionized the marketing scenario. Although there are numerous researches on the impact of SMM, but there is nothing specific to understand its impact on White goods brands and this gap area has been addressed through literature review and conceptual understanding of terms Social Media Marketing, Consumer Based Brand Equity, Purchase Intention and also researches done for other industries.